Patient Characteristics and Antithrombotic Prescribing Patterns in Patients with Atrial Fibrillation in Tasmania - Bista, D.; Chalmers, Leanne; Peterson, G.; Bereznicki, L. (2017)
© 2017 SAGE Publications. Limited data are available on atrial fibrillation (AF) and its clinical management and outcomes from an Australian perspective. This study was designed to examine the patient characteristics and antithrombotic treatment patterns among patients with AF in Tasmania, Australia. This retrospective observational study reviewed and followed patients with AF admitted to Tasmania's 3 major hospitals between January 2011 and June 2012. Patients were excluded if they had only 1 episode of AF that reverted spontaneously or upon cardioversion without any documented recurrences. We reviewed the records of 2502 patients (=18 years), and1469 were subsequently included in the study. The mean (±standard deviation [SD]) age of the patients was 76 (±12.3) years. The mean (± SD) CHADS 2 score was 2.1 (±1.3), and 65.7% had a score =2. In total, only 55.6% of patients with CHADS 2 score =2 were receiving anticoagulation and 9.9% were not receiving any antithrombotic treatment, whereas 85.4% of those at low risk (score 0) were on antithrombotic therapy. Hospitalization was associated with a significant increase in the rate of combination (antiplatelet plus anticoagulant) therapy (P < .001). Suboptimal use of antithrombotic therapy highlights the need to improve AF management in our jurisdiction.